Preparation of an Excellent Z‐type SrWO4@Bi2WO6 Heterojunction Photocatalyst and Its Photocatalytic Performance under Simulated Sunlight. Issue 34 (13th September 2021) - Guo, Bobo; Gu, Yufen
Abstract: In this work, a simple chemical co‐precipitation method was employed to prepare a series of excellent Z‐type SrWO4 @Bi2 WO6 (SWO@BWO) heterojunction composites, in which SrWO4 was successfully assembled on Bi2 WO6 nanosheets. The outstanding separation efficiency of photo‐generated carriers (e − /h + ) originated from synergetic effect of semiconductor heterojunctions under simulated sunlight effectively improved photocatalytic activity, resulting in a more prominent performance for organic dyestuff degradation compared with its counterparts. Based on the photocatalytic degradation of Methylene blue (MB) experiment, coming to a conclusion is that 10wt %SWO@BWO composite (η=92.9 % for 50 min) has the prominent photocatalytic activity. The photocatalytic performance of 10wt %SWO@BWO composite is 6.36 and 2.6 times as high as that of bare SWO and BWO, respectively. This composite also has better degradation performance for Tetracycline Hydrochloride (TC) and Tetrabromobisphenol A (TBBPA). According to the active species capture experiment, . OH are dominant in the degradation process of MB, and role of h + and . O2 − is also indispensable. Our research provides a simple approach for establishing Z‐scheme heterojunction photocatalysts with great photocatalytic performance. Abstract : The 10wt %SWO@BWO heterostructure catalyst prepared by two step method (hydrothermal method+co‐precipitation method) has the best degradation performance of MB, and the degradation rate of MB is up to 92.9 % within 50 minutes. The Z‐type charge transfer mechanism formed under simulated sunlight improves the separation efficiency of photogenerated carriers, further prolongs the existence life of photogenerated carriers, and facilitates the effective participation of photogenerated electrons and holes in the photodegradation of MB.